Hepatocellular adenoma: an excellent indication for laparoscopic liver resection - Herman, Paulo (Blackwell Publishing Ltd, 2012)
OBJECTIVES: Laparoscopic resection for benign liver disease has gained wide acceptance in recent years and hepatocellular adenoma (HA) seems to be an appropriate indication. This study aimed to discuss diagnosis and treatment strategies, and to assess the feasibility, safety and outcomes of pure laparoscopic liver resection (LLR) in a large series of patients with HA. METHODS: Of 88 patients who underwent pure LLR, 31 were identified as having HA. Diagnosis was based on radiological evaluation and resections were performed for lesions measuring >5.0 cm. RESULTS: The sample included 29 female and two male patients. Their mean age was 33.2 years. A total of 27 patients had a single lesion, one patient had two and one had four lesions. The two remaining patients had liver adenomatosis. Mean tumour size was 7.5 cm. Three right hepatectomies, 17 left lateral sectionectomies and 11 wedge resections or segmentectomies were performed. There was no need for blood transfusion or conversion to open surgery. Postoperative complications occurred in two patients. Mean hospital stay was 3.8 days. CONCLUSIONS: Hepatocellular adenoma should be regarded as an excellent indication for pure LLR. Pure LLR is safe and feasible and should be considered the standard of care for the treatment of HA when performed by surgeons with experience in liver and laparoscopic surgery.